UPAYA MENJAGA WARISAN BUDAYA DI TENGAH ARUS GLOBALISASI - Fahmi Zulfa Fadilla, Hikmah Alfiyah, Maftucha (Universitas Negeri Semarang, 2025)
Globalization brings complex changes that challenge the sustainability of cultural heritage in Indonesia. This raises concerns about cultural uniformity, the shift of traditional values towards more individualism, and the declining attention of the younger generation to local wisdom. This study aims to explore ways to preserve national cultural heritage amidst the rapid flow of globalization. The method used is desk research with qualitative data analysis through data reduction and drawing conclusions from various relevant sources. The research findings indicate that efforts to preserve cultural heritage require strong collaboration between government policies, such as Law No. 5 of 2017, active community involvement, and the role of cultural communities. In addition, the use of digital technologies such as 3D documentation, social media, and innovations such as Augmented Reality (AR) are important tools in promoting culture to generations Z and Alpha. The conclusion of this study is that with a comprehensive and adaptive approach, globalization does not have to destroy local identity, but can be a means of revitalization to ensure cultural heritage remains relevant for future generations.